Stretchable electromagnetic shielding fabric and preparation method and application thereof

By growing PDA and silver nanoparticles on the surface of TPU fabric and forming a double-pleated structure, the problem of easy destruction of the conductive network in traditional conductive fabrics under deformation conditions is solved, and stable conductivity and electromagnetic shielding performance under tensile, twisting and bending conditions are achieved.

CN119571620AActive Publication Date: 2025-03-07ZHENGZHOU UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411738768.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-07
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

When traditional conductive fabrics suffer from deformation such as stretching, twisting and bending, the conductive network is easily destroyed, resulting in a significant decrease in shielding efficiency.

Method used

TPU fabric is used as a matrix, TPU fibers are prepared by electrospinning technology, and PDA and silver nanoparticles are grown on their surface to form a double-wrinkle structure to enhance the elasticity and conductivity of the fabric.

Benefits of technology

Under deformation conditions, the macro-pleats and micro-pleats of TPU/PDA/W-Ag fabric jointly protect the conductive network, keeping the conductivity and electromagnetic shielding performance unchanged, significantly improving the stretchability and stability of the fabric.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571620A_ABST
    Figure CN119571620A_ABST
Patent Text Reader

Abstract

The invention discloses a stretchable electromagnetic shielding fabric and a preparation method and application thereof. Comprising a TPU fabric, the TPU fabric is composed of a plurality of TPU fibers, and PDA and silver nanoparticles grow on the surface of the TPU fabric; the stretchable electromagnetic shielding fabric has a macroscopic and microscopic double-fold structure. The preparation method comprises the following steps: (1) dissolving TPU in a DMF / THF mixed solvent, and carrying out electrostatic spinning to obtain a TPU fabric; (2) dissolving dopamine hydrochloride powder and Tris-HCl powder in water, stirring to form a solution with the pH value of 8-9, putting the TPU fabric into the solution, continuously stirring, taking out the TPU fabric, and carrying out ultrasonic treatment to obtain TPU / PDA fabric; and (3) dissolving CF3COOAg in water, then immersing, taking out and drying the TPU / PDA fabric which is pre-stretched by applying pre-stretching stress in advance, then immersing the TPU / PDA fabric into a water diluent of hydrazine hydrate for 10-20 minutes, taking out and releasing the pre-stretching stress to obtain a target product. The stretchable electromagnetic shielding fabric is applied to intelligent portable electronic equipment. The fabric has good cyclic tensile property and electromagnetic shielding property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of stretchable electromagnetic shielding materials, and in particular relates to a stretchable electromagnetic shielding fabric and a preparation method and application thereof. Background Art

[0002] With the rapid development of 5G communication technology, smart portable electronic devices are constantly progressing towards integration and miniaturization. However, this progress has also brought about electromagnetic interference (EMI) and radiation problems, which affect the normal functions of electronic devices and pose a potential threat to human health, especially the health of pregnant women and sensitive people. Conductive fabrics have gradually become ideal electromagnetic shielding materials in wearable electronic products due to their light, flexible and wearable characteristics. Conductive fabrics can not only be used to shield electromagnetic interference, but also can be used as multifunctional materials such as health monitoring and temperature management, and have broad application prospects in future smart devices.

[0003] However, when traditional conductive fabrics are subjected to deformation such as stretching, twisting and bending, the significant modulus difference between the elastic matrix and the rigid conductive network easily leads to the destruction of the conductive network, which in turn causes a significant decrease in shielding effectiveness. Faced with this challenge, the development of stretchable electromagnetic shielding fabrics that can maintain stable performance under deformation conditions has become a technical problem that needs to be solved urgently. Summary of the invention

[0004] In order to overcome the disadvantage that the traditional conductive fabric has unstable performance under deformation conditions, the purpose of the present invention is to provide a stretchable electromagnetic shielding fabric that can still maintain stable performance under deformation conditions, and a preparation method and application thereof.

[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows: A stretchable electromagnetic shielding fabric comprises a TPU fabric, wherein the TPU fabric is composed of a plurality of TPU fibers, and PDA and silver nanoparticles are grown on the surface of the TPU fabric; the stretchable electromagnetic shielding fabric has a double fold structure, namely, macroscopic folds on the surface of the TPU fabric and microscopic folds on the surface of a single TPU fiber; wherein the TPU is thermoplastic polyurethane, and the PDA is polydopamine.

[0006] The preparation method of the stretchable electromagnetic shielding fabric comprises the following steps: (1) dissolving TPU in a DMF / THF mixed solvent to obtain an electrospinning solution, and then electrospinning to obtain TPU fabric; (2) Dissolve dopamine hydrochloride powder and Tris-HCl powder in water, stir evenly to form a solution with a pH of 8-9, put the TPU fabric in to completely immerse it, continue stirring for 12-18 hours, take it out and remove the agglomerated PDA by ultrasonication in water to obtain TPU / PDA fabric; (3) dissolving CF3COOAg in water to prepare a silver precursor solution; (4) applying pre-stretching stress to the TPU / PDA fabric in advance for pre-stretching, then immersing the pre-stretched TPU / PDA fabric in a silver precursor solution, taking it out and drying it in air to obtain a pre-stretched TPU / PDA fabric containing a silver precursor; (5) Immerse the pre-stretched TPU / PDA fabric containing the silver precursor in a water-diluted solution of hydrazine hydrate for 10 to 20 minutes, take it out, and completely release the pre-stretching stress to obtain the target product - stretchable electromagnetic shielding fabric.

[0007] Preferably, in step (1), the DMF / THF mixed solvent consists of DMF and THF in a volume ratio of 1:(1-3); and the concentration of TPU in the electrospinning solution is 10-20wt%.

[0008] Preferably, in step (1), the electrospinning parameters are: spinning voltage 10-20 kV, distance between needle and roller collector 10-20 cm, injection rate 1-3 mL / h, humidity 40±10 RH%, temperature 30±5°C.

[0009] Preferably, in step (2), when the dopamine hydrochloride powder and the Tris-HCl powder are dissolved in water, the concentration of Tris-HCl is 4-6 g / L, and the concentration of dopamine hydrochloride is 1-2 g / L.

[0010] Preferably, in step (3), the concentration of CF3COOAg in the silver precursor solution is 0-20wt% but does not include 0.

[0011] Preferably, in step (4), a pre-stretching stress is applied to the TPU / PDA fabric in advance to pre-stretch the fabric to a pre-stretching ratio of 100% to 300%. The pre-stretching ratio refers to the ratio of the length change before and after pre-stretching to the original length before pre-stretching.

[0012] Preferably, in step (5), the concentration of hydrazine hydrate in the water dilution of hydrazine hydrate is 10-20 wt %.

[0013] Application of the stretchable electromagnetic shielding fabric in intelligent portable electronic devices.

[0014] Beneficial effects: (1) The TPU / PDA / W-Ag fabric of the present invention has good hydrophobicity, which is because the silver nanoparticles form a rough surface structure on the fiber surface, and the silver nanoparticles themselves have a low surface energy; in addition, the macroscopic wrinkles of the TPU fabric and the microscopic wrinkles on the surface of a single TPU fiber also improve the hydrophobicity; (2) The TPU / PDA / W-Ag fabric of the present invention has good air permeability, mechanical properties and cyclic tensile properties, and can be used in wearable intelligent portable electronic equipment products; (3) When the TPU / PDA / W-Ag fabric is deformed, the macro-wrinkles of the TPU / PDA / W-Ag fabric are stretched first. When the strain increases, the micro-wrinkles on the single TPU fiber begin to work and stretch as the strain increases. Therefore, the macro-wrinkles of the TPU fabric and the micro-wrinkles of the single TPU fiber work together to protect the conductive network from being destroyed during the stretching process, thereby achieving unchanged conductivity under deformation conditions and excellent stretchable electromagnetic shielding performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 Microscopic morphology of the products obtained in Example 1 and Control Example 1: (a) TPU fabric; (b) TPU / PDA fabric; (c) SEM image of TPU / PDA / Ag fabric and (d) regional magnification; (e, e1) SEM images of TPU / PDA / W-Ag fabrics obtained with a pre-stretching ratio of 100%, (f, f1) 200%, and (g, g1) 300%; (h) SEM cross-sectional image of TPU / PDA / Ag fabric and (i) EDS element mapping of Ag, N, C, and O.

[0016] Figure 2 : The water contact angles of the products obtained in Example 1 and Control Example 1. The abscissas TPU, 0, 100, 200, and 300 in the figure represent TPU fabric, TPU / PDA / Ag (pre-stretching ratio 0%), and TPU / PDA / W-Ag fabric obtained with pre-stretching ratios of 100%, 200%, and 300%, respectively.

[0017] Figure 3 The air permeability performance diagram of the TPU / PDA / W-Ag fabric obtained with a pre-stretching ratio of 300% in Example 1: (a) Comparison of the air permeability of plastic wrap (Parafilm) and TPU / PDA / W-Ag fabric; (b) The curve of the change of the mass of water in the bottle over time and (c) the permeability when the small bottle is in the open state (Opened) and covered with plastic wrap (Sealed), TPU fabric, and TPU / PDA / W-Ag (pre-stretching ratio 300%) fabric.

[0018] Figure 4The mechanical properties and cyclic tensile properties of the products obtained in Example 1 and Control Example 1 are as follows: (a) stress-strain curves of TPU fabric and TPU / PDA / W-Ag fabric obtained with different pre-stretching ratios; (b) cyclic stress-strain curves of TPU / PDA / W-Ag fabric obtained with a pre-stretching ratio of 300% under different strains.

[0019] Figure 5 The conductivity of the TPU / PDA / W-Ag fabric obtained with a pre-stretching ratio of 300% in Example 1 under various deformation conditions.

[0020] Figure 6 The resistance (a) and the change of resistance with strain (b) of the products obtained in Example 1 and Comparative Example 1.

[0021] Figure 7 The electromagnetic shielding performance of the products obtained in Example 1 and Comparative Example 1: (a) electromagnetic shielding effectiveness (EMISE); (b) total electromagnetic shielding effectiveness (SE T ), reflection efficiency (SE R ), absorption efficiency (SE A ); (cf) EMI SE changes under different stretching conditions.

[0022] Figure 8 The electromagnetic shielding performance of the TPU / PDA / W-Ag fabric obtained with a pre-stretching ratio of 300% in Example 1 under the condition of 100% strain and 0, 10, 100 and 500 stretch-release cycles.

[0023] Fig. 9 SEM images of the TPU / PDA / Ag fabric obtained in Control Example 1 and the TPU / PDA / W-Ag fabric obtained in Example 1 with a pre-stretching ratio of 300% at the initial state (a, d), 50% strain (b, e) and 100% strain (c-c1, f-f1), respectively. DETAILED DESCRIPTION

[0024] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described below in conjunction with specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Based on the described embodiments, all other embodiments obtained by those skilled in the art without creative work belong to the protection scope of the present invention.

[0025] Example 1

[0026] A stretchable electromagnetic shielding fabric comprises a TPU fabric, wherein the TPU fabric is composed of a plurality of TPU fibers, and PDA and silver nanoparticles are grown on the surface of the TPU fabric; the stretchable electromagnetic shielding fabric has a double fold structure, namely, macroscopic folds on the surface of the TPU fabric and microscopic folds on the surface of a single TPU fiber; wherein the TPU is thermoplastic polyurethane, and the PDA is polydopamine.

[0027] The preparation steps are as follows: (1) Dissolve TPU in a DMF / THF (N,N-dimethylformamide / tetrahydrofuran) mixed solvent (volume ratio, DMF and THF = 1:1) to obtain an electrospinning solution with a TPU concentration of 20 wt%, and then electrospin to obtain TPU fabric; wherein the electrospinning parameters are: spinning voltage 15 kV, the distance between the needle and the roller collector 15 cm, injection rate 3 mL / h, humidity 40 RH%, temperature 30 ° C; (2) Dissolve dopamine hydrochloride powder and Tris-HCl powder in deionized water. The concentration of Tris-HCl powder is 5 g / L and the concentration of dopamine hydrochloride is 1.4 g / L. Stir evenly to form a mixed solution with a pH of 8.5. Add TPU fabric so that it is completely immersed. Stir continuously for 12 h. Dopamine polymerizes into polydopamine (PDA). After taking it out, ultrasonicate it in water for 5 min to remove the agglomerated PDA, and obtain TPU / PDA fabric. (3) dissolving CF3COOAg (silver trifluoroacetate) in water to prepare a silver precursor solution having a CF3COOAg concentration of 20 wt%; (4) applying pre-stretching stress to the TPU / PDA fabric in advance to pre-stretch the fabric to a pre-stretching ratio of 100%, 200% and 300%, respectively, and then immersing the pre-stretched TPU / PDA fabric in a silver precursor solution for 10 minutes, taking it out and drying it in air for 5 minutes to obtain a pre-stretched TPU / PDA fabric containing a silver precursor; (5) The pre-stretched TPU / PDA fabric containing silver precursor was immersed in a 10wt% aqueous solution of hydrazine hydrate for 10 min. The silver ions on the fiber surface were reduced to silver nanoparticles (AgNPs). The fabric was taken out and the pre-stretching stress was completely released to obtain the target product - stretchable electromagnetic shielding fabric, which was marked as TPU / PDA / W-Ag fabric.

[0028] Comparative Example 1 The difference from Example 1 is that in step (4), no pre-stretching stress is applied to the TPU / PDA fabric in advance for pre-stretching, that is, the pre-stretching ratio is 0%. The specific preparation steps are as follows: (1) Same as step (1) in Example 1; (2) Same as step (2) in Example 1; (3) Same as step (3) in Example 1; (4) directly immersing the TPU / PDA fabric in the silver precursor solution for 10 minutes, taking it out and drying it in air for 5 minutes to obtain the TPU / PDA fabric containing the silver precursor; (5) The TPU / PDA fabric containing the silver precursor was immersed in a 10 wt% aqueous solution of hydrazine hydrate for 10 min. The silver ions on the fiber surface were reduced to silver nanoparticles (AgNPs). The fabric was taken out and the pre-stretching stress was completely released to obtain a control product, which was marked as TPU / PDA / Ag fabric.

[0029] Product structure characterization Figure 1 Microscopic morphology of the products obtained in Example 1 and Control Example 1: (a) TPU fabric; (b) TPU / PDA fabric; (c) SEM image of TPU / PDA / Ag fabric and (d) regional magnification; (e, e1) SEM images of TPU / PDA / W-Ag fabrics obtained with a pre-stretching ratio of 100%, (f, f1) 200%, and (g, g1) 300%; (h) SEM cross-sectional image of TPU / PDA / Ag fabric and (i) EDS element mapping of Ag, N, C, and O.

[0030] like Figure 1 As shown in (a), the initial surface of the TPU fabric is smooth and the fiber diameter is about 3 μm; Figure 1 As shown in (b), after the PDA layer self-polymerizes on the fiber surface, the fiber surface becomes rough; then, as Figure 1 As shown in (c), Ag nanoparticles are uniformly reduced on the surface of TPU / PDA fibers. Figure 1 As shown in (i), the existence of AgNPs was confirmed by EDS element mapping images; Figure 1 As shown in (e, e1-g, g1), compared with the non-pre-stretched TPU / PDA / Ag fabric, the pre-stretched TPU / PDA fiber presents a macroscopic block wrinkle structure on the surface after release, and a microscopic wrinkle structure appears on the surface of a single fiber. As the pre-stretching ratio increases from 100% to 300%, the period of macroscopic and microscopic wrinkles gradually shortens, while the compactness increases, which is attributed to the increase in shrinkage deformation under high pre-stretching conditions.

[0031] Product performance characterization 1. Hydrophobicity Figure 2The water contact angles of the products obtained in Example 1 and Comparative Example 1, in which the horizontal axes TPU, 0, 100, 200, and 300 respectively represent TPU fabric, TPU / PDA / Ag (pre-stretching ratio 0%), and TPU / PDA / W-Ag fabric obtained with pre-stretching ratios of 100%, 200%, and 300%. Figure 2 As shown, all products have hydrophobic properties, and the water contact angle (WCA) of the TPU / PDA / W-Ag fabric obtained with a pre-stretching ratio of 300% can reach 131.8°.

[0032] (ii) Breathability The air permeability of the TPU / PDA / W-Ag fabric obtained with a pre-stretching ratio of 300% in Example 1 was tested. Take eight small bottles of the same size and mark them as 1#, 2#, 3#, 4#, 5#, 6#, 7#, and 8# in sequence, wherein 10 mL of 36 wt% hydrochloric acid is equally filled into the 1# and 2# small bottles, and the mouth of the 1# small bottle is covered with plastic wrap, the mouth of the 2# small bottle is covered with TPU / PDA / W-Ag fabric obtained with a pre-stretching ratio of 300%, 10 mL of 25 wt% ammonia water is equally filled into the 3# and 4# small bottles, respectively; 10 mL of water is equally filled into the 5#, 6#, 7#, and 8# small bottles, and the mouth of the 5# small bottle is kept open, the mouth of the 6# small bottle is covered with plastic wrap, the mouth of the 7# small bottle is covered with TPU fabric, and the mouth of the 8# small bottle is covered with TPU / PDA / W-Ag fabric obtained with a pre-stretching ratio of 300%.

[0033] After the experiment started, first place two pH test papers close to 1# and 2# small bottles filled with hydrochloric acid, and observe the color change of the pH test papers. Then place 1# and 2# small bottles filled with hydrochloric acid close to 3# and 4# small bottles filled with ammonia, and observe whether there is white smoke above 1# and 2# small bottles filled with hydrochloric acid. At the beginning of the experiment, weigh and record the weight of 5#, 6#, 7# and 8# small bottles, and then weigh and record them every 0.5h. By comparing the weight difference of the small bottles at different times and at the beginning of the experiment, convert the weight of the gas permeated into the four small bottles at different times.

[0034] Figure 3 The air permeability performance diagram of the TPU / PDA / W-Ag fabric obtained with a pre-stretching ratio of 300% in Example 1: (a) Comparison of the air permeability of the cling film (Parafilm) and the TPU / PDA / W-Ag fabric; (b) The curve of the mass of water in the bottle changing with time when the small bottle is opened (Opened) and covered with cling film (Sealed), TPU fabric, and TPU / PDA / W-Ag (pre-stretching ratio 300%) fabric, and (c) the permeability. Figure 3As shown in (a), when the bottle mouth is covered with plastic wrap, the pH test paper does not change color when it is close to the bottle. When the bottle mouth is covered with TPU / PDA / W-Ag fabric, the pH test paper changes color when it is close to the bottle. Similarly, when the bottle containing hydrochloric acid is covered with plastic wrap and TPU / PDA / W-Ag fabric and close to the bottle containing ammonia water, there is no change above the bottle covered with plastic wrap, and white smoke appears above the bottle covered with TPU / PDA / W-Ag fabric, indicating that hydrochloric acid reacts with ammonia water through TPU / PDA / W-Ag fabric, which shows that TPU / PDA / W-Ag fabric has excellent gas permeability; Figure 3 (bc) Quantitatively demonstrate the good gas permeability of TPU / PDA / W-Ag fabric, which is close to that of pure TPU fabric.

[0035] (III) Mechanical properties and cyclic tensile properties Figure 4 The mechanical properties and cyclic tensile properties of the products obtained in Example 1 and Comparative Example 1 are as follows: (a) stress-strain curves of TPU fabric and TPU / PDA / W-Ag fabrics obtained with different pre-stretching ratios; (b) cyclic stress-strain curves of TPU / PDA / W-Ag fabrics obtained with a pre-stretching ratio of 300% under different strains. Figure 4 As shown in (a), in terms of mechanical properties, the tensile strength of the TPU / PDA / W-Ag fabrics obtained after different pre-stretching ratios is not much different from that of the original TPU fabric, and the elongation is slightly reduced, which meets the application conditions. Figure 4 As shown in (b), the cyclic stretch-release experiment shows that the fabric has excellent stretch recovery performance.

[0036] (IV) Electrical conductivity The conductivity of the TPU / PDA / W-Ag fabric obtained with a pre-stretching ratio of 300% in Example 1 was tested: the TPU / PDA / W-Ag fabric was used as a conductor in a circuit, a light bulb and a power switch were connected in series, and then the brightness characteristics of the light bulb were observed under different deformation conditions (including original, stretch, bend, twist, and stretch and twist) of the TPU / PDA / W-Ag fabric as a conductor. Figure 5 The conductivity of the TPU / PDA / W-Ag fabric obtained with a pre-stretching ratio of 300% in Example 1 under various deformation conditions. The stretching percentage in the figure refers to the ratio of the length change before and after stretching to the original length before stretching. Figure 5 As shown, it was observed that under different deformation conditions, the light bulb was bright when the switch was turned on, and the brightness of the light bulb did not change much under different deformation conditions, which verified that the TPU / PDA / W-Ag fabric maintained stable conductivity under various deformation conditions.

[0037] Figure 6 The resistance (a) and the change of resistance with strain (b) of the products obtained in Example 1 and Comparative Example 1 are shown. Figure 6 As shown in (a), the resistance of TPU / PDA / W-Ag fabric decreases with the increase of pre-stretching ratio. Figure 6 As shown in (b), for the TPU / PDA / Ag fabric without pre-stretching (pre-stretching ratio 0%), when the strain increases from 0% to 50%, the resistance shows a significant growth trend, increasing from 10.95Ω / sq to 471.41Ω / sq. For the TPU / PDA / W-Ag fabric obtained with a pre-stretching ratio of 100%, the resistance remains almost unchanged until the strain reaches a critical value of about 50%. Thereafter, the resistance increases rapidly. As the pre-stretching ratio increases, the critical strain value also increases. When the pre-stretching ratio reaches 300%, the critical strain value exceeds 100%.

[0038] (V) Electromagnetic shielding performance Figure 7 The electromagnetic shielding performance of the products obtained in Example 1 and Comparative Example 1: (a) electromagnetic shielding effectiveness (EMISE); (b) total electromagnetic shielding effectiveness (SE T ), reflection efficiency (SE R ), absorption efficiency (SE A ); (cf) EMI SE changes under different stretching conditions. Figure 7 As shown in (a), when there is no pre-stretching, the electromagnetic shielding effectiveness of the TPU / PDA / Ag fabric is 57.9 dB. As the pre-stretching ratio increases, the EMI SE value also increases. Figure 7 (c) shows that when the strain reaches 50%, the EMI SE of the TPU / PDA / Ag fabric drops sharply to below 10 dB and loses its electromagnetic shielding performance at 100% strain. Figure 7 (df) shows the changes in EMI SE of TPU / PDA / W-Ag fabrics obtained with pre-stretching ratios of 100%, 200% and 300% under different stretching conditions. With the increase of strain, EMI SE gradually decreases. For TPU / PDA / W-Ag fabrics obtained with a pre-stretching ratio of 100%, its EMISE slowly decreases from 61.7dB to 16.7dB as the strain increases from 0% to 100%. In addition, under the same tensile strain conditions, with the increase of pre-stretching ratio, the EMI SE value also increases accordingly. At a pre-stretching ratio of 300%, the EMI SE of TPU / PDA / W-Ag fabric under 100% strain remains at about 36dB.

[0039] The TPU / PDA / W-Ag fabric obtained with a pre-stretching ratio of 300% in Example 1 was used as the object, and a cyclic stretching and release test was carried out under 100% strain to evaluate the stability of its electromagnetic shielding performance. Figure 8 The electromagnetic shielding performance of the TPU / PDA / W-Ag fabric obtained with a pre-stretching ratio of 300% in Example 1 under the condition of 100% strain at 0, 10, 100 and 500 stretch-release cycles. Figure 8 As shown, the EMI SE of the TPU / PDA / W-Ag fabric with a pre-stretching ratio of 300% remained above 65 dB after 500 cycles.

[0040] (VI) Micromorphology under different strain conditions Fig. 9 The SEM images of the TPU / PDA / Ag fabric obtained in Control Example 1 and the TPU / PDA / W-Ag fabric obtained in Example 1 with a pre-stretching ratio of 300% at the initial state (a, d), 50% strain (b, e) and 100% strain (c-c1, f-f1). For the TPU / PDA / Ag fabric without pre-stretching, it presents a continuous AgNPs conductive network in the initial state ( Fig. 9 a), As the strain increases (50%→100%), the AgNPs on the fiber begin to separate ( Fig. 9 b), and finally the conductive network composed of AgNPs is completely destroyed ( Fig. 9 c-c1). For TPU / PDA / W-Ag fabric, it exhibits a periodic macroscopic wrinkled structure in the initial state, and the microscopic wrinkled AgNPs conductive network is wrapped around each fiber ( Fig. 9 d) When the TPU / PDA / W-Ag fabric is stretched, the wrinkled structure unfolds, while the wrinkled AgNPs can still maintain a conductive network at 50% strain ( Fig. 9 e) When the strain continues to increase to 100%, the periodic macroscopic wrinkle structure is fully unfolded, and the wrinkled AgNPs conductive network on the fiber begins to function ( Fig. 9 f-f1).

Claims

1. A stretchable electromagnetic shielding fabric, characterized in that: The invention comprises a TPU fabric, wherein the TPU fabric is composed of a plurality of TPU fibers, and PDA and silver nanoparticles are grown on the surface of the TPU fabric; the stretchable electromagnetic shielding fabric has a double fold structure, namely, macroscopic folds on the surface of the TPU fabric and microscopic folds on the surface of a single TPU fiber; wherein the TPU is thermoplastic polyurethane, and the PDA is polydopamine.

2. A method for preparing the stretchable electromagnetic shielding fabric according to claim 1, characterized in that: Here are the steps: (1) dissolving TPU in a DMF / THF mixed solvent to obtain an electrospinning solution, and then electrospinning to obtain TPU fabric; (2) Dissolve dopamine hydrochloride powder and Tris-HCl powder in water, stir evenly to form a solution with a pH of 8-9, put the TPU fabric in to completely immerse it, continue stirring for 12-18 hours, take it out and remove the agglomerated PDA by ultrasonication in water to obtain TPU / PDA fabric; (3) dissolving CF3COOAg in water to prepare a silver precursor solution; (4) applying pre-stretching stress to the TPU / PDA fabric in advance for pre-stretching, then immersing the pre-stretched TPU / PDA fabric in a silver precursor solution, taking it out and drying it in air to obtain a pre-stretched TPU / PDA fabric containing a silver precursor; (5) Immerse the pre-stretched TPU / PDA fabric containing the silver precursor in a water-diluted solution of hydrazine hydrate for 10 to 20 minutes, take it out, and completely release the pre-stretching stress to obtain the target product - stretchable electromagnetic shielding fabric.

3. The method for preparing the stretchable electromagnetic shielding fabric according to claim 1, characterized in that: In step (1), the DMF / THF mixed solvent is composed of DMF and THF in a volume ratio of 1:(1-3); in the electrospinning solution, the concentration of TPU is 10-20wt%.

4. The method for preparing a stretchable electromagnetic shielding fabric according to claim 1, characterized in that: In step (1), the electrospinning parameters are: spinning voltage 10-20 kV, distance between needle and roller collector 10-20 cm, injection rate 1-3 mL / h, humidity 40±10 RH %, temperature 30±5°C.

5. The method for preparing the stretchable electromagnetic shielding fabric according to claim 1, characterized in that: In step (2), when dopamine hydrochloride powder and Tris-HCl powder are dissolved in water, the concentration of Tris-HCl is 4-6 g / L, and the concentration of dopamine hydrochloride is 1-2 g / L.

6. The method for preparing a stretchable electromagnetic shielding fabric according to claim 1, characterized in that: In step (3), the concentration of CF3COOAg in the silver precursor solution is 0-20wt% but does not include 0.

7. The method for preparing a stretchable electromagnetic shielding fabric according to claim 1, characterized in that: In step (4), pre-stretching stress is applied to the TPU / PDA fabric in advance to pre-stretch the fabric to a pre-stretching ratio of 100% to 300%.

8. The method for preparing a stretchable electromagnetic shielding fabric according to claim 1, characterized in that: In step (5), the concentration of hydrazine hydrate in the water dilution of hydrazine hydrate is 10-20wt%.

9. Use of the stretchable electromagnetic shielding fabric as claimed in claim 1 in intelligent portable electronic devices.

Citation Information

Patent Citations

  • Preparation method of double-conductive-network super-hydrophobic fabric strain sensor

    CN115748241A

  • High-performance flexible carbon nanotube conductive composite fiber and preparation method thereof

    CN116219573A

  • Tensile conductive yarn and manufacturing method therefor

    WO2022089510A1